ヒョウショウ ヒョウガ ノ コア カイセキ ニ ヨル ネンダイ スイテイ ホウホウ - 藤井, 理行; フジイ, ヨシユキ; 神山, 孝吉; カミヤマ, コウキチ; 渡辺, 興亜; ワタナベ, オキツグ; Fujii, Yoshiyuki; Kamiyama, Koukichi; Watanabe, Okitsugu (1989)
P(論文) 氷床や氷河の涵養域では, 積雪のみならず, 地上起源, 宇宙起源および人間活動に起因するさまざまな物質が堆積し, 地球の気候および環境の変動の良き記録となっている。こうした過去の記録の復元のために, 極地の氷床や各地の氷河では雪氷コアの掘削が行われており, コアの年代決定やコアからの堆積環境復元の試みがなされている。本報文では, 南極や北極で得られたコアについての実際の解析に即して, 特に堆積年代の合理的な推定方法の確立をはかりつつ, これまで試みられてきたコア解析の方法を, (i)コアの第一次処理の方法, (ii)機器分析法, (iii)層位解析の方法, および(iv)示準層の検出方法について紹介し, その有効性, 問題点をのべる。 Snow-ice cores obtained from ice sheets and glaciers are formed from deposited snow and other materials of terrestrial, cosmic and artificial origin. Depositional mode of these materials is presumed to be a good indicator of climatic and environmental changes during the past several 10^0-10^5 years. On the other hand, core dating methods have not been well established. In this paper, sample preparation procedures, instrumental analyses, active and stable isotope analyses, and stratigraphic analysis relating to the core dating are reviewed with reference to cores obtained from the Antarctic and Arctic. departmental bulletin paper